Eksaminasi Terhadap Putusan Mahkamah Konstitusi Nomor 1/PHPU.PRES-XXII/2024 - Ristiawati, Risni; Faraby Hafifullhaq, Farez; Syahalam, Gusti Muhammad; Hafizh, Muhammad; Sihombing, Yuri Sebrina (Banua Law Review, 2024)
The iCourt istated ithat ithere iwas ino ilegal ibasis ifor iAnies-Muhaimin's iargument iregarding ithe iappointment iof ia iselection iteam ifor imembers iof ithe iGeneral iElection iCommission i(KPU) iand imembers iof ithe iGeneral iElection iSupervisory iBody i(Bawaslu) iby ithe iPresident iin iviolation iof iArticle i22 iparagraph i(3) iof ithe iElection iLaw ibecause iit iincluded igovernment ielements iof imore ithan ithree ipeople. i. iThe iCourt ifound ino ifact iof iobjection ifrom ithe iDPR iregarding ithe icomposition iof ithe iselection iteam imembers. iIn ifact, isome iof ithe iDPR ifactions, iwhich iare ian iextension iof ithe ipolitical iparty isupporting iAnies-Muhaimin, ishould ihave ibeen iable ito iraise iobjections ifrom ithe istart. iHowever, ieven iif iit iis itrue ithat ithere iare imore ithan ithree igovernment ielements, iit iis idifficult ifor ithe iCourt ito ifind ia icorrelation ibetween ithis inumber iand ithe iindependence iof iKPU imembers ior iBawaslu imembers iin icarrying iout itheir iduties iin iorganizing ielections. iMoreover, iit iis ialso idifficult ifor ithe iCourt ito ifind ia icorrelation ibetween ithe inumber iof ielements iof ithe iselection iteam iand ithe ivotes iobtained iby ithe ipresidential iand ivice ipresidential icandidates iin ithe i2024 iElection. iAccording ito ithe iCourt, iBawaslu imust iinclude ithe isubstance iof ithe ireport ior ifindings ito iprove iwhether ior inot ithere ihave ibeen isubstantial ielection iviolations. iincluding iregional ihead ielections i(pilkada/pemilukada). iThis imeans ithat iif ithese ichanges iare inot imade, ithis iwill ithreaten ithe irealization iof ielections ithat iare ihonest, ifair iand ihave iintegrity. iWith ia ithreat ilike ithat, iit icould icause iBawaslu ito ilose iits iexistence ias ian ielection imonitoring iinstitution ito irealize ielections ithat iare ihonest, ifair iand ihave iintegrity.